Physics Textbooks Feature Augmented Reality Technology-Based Media For Kinematics Material: Training 21st Century Skills For High School Students - Bakri, Fauzi; Sani, Tiara Nurmalita; Permana, Handjoko (Current STEAM and Education Research, 2023)
Textbook as the main medium of learning are required to meet the needs of the 21st century. Textbook must facilitate the formation of 21st century skills. The necessary skills are Critical Thinking, Communication, Collaboration, and Creativity. This article describes the results of research on the development of a physics textbook at kinematic concept with augmented reality technology-based media. The physics textbook of this research is aimed at practicing the 21st century skills of high school students. The research method used is research and development with a Dick and Carey approach. A physics textbook at kinematic concept has been produced with stages to practice in 21st century skills. The components presented are: video based on augmented reality technology, data tables, graphs, pictures, mathematical analysis, verbal analysis for each subtopic presented. Learning is based on four pillars of education, namely: learning to know, learning to do, learning to be, and learning how to live together. The stages in the structure of the book being developed are concept maps, preliminary knowledge tests, theory by providing competency tests in each sub-chapter, summary, reflection, chapter competency tests, and learning activities that contain 4C components in practicing 21st century skills keterampilan. The results of this research and development textbook physics at kinematic concept have been validated by physics material experts, learning experts and textbook media experts. The expert gives a very decent assessment for all aspects that are assessed.